Comparative Analysis of Short-Term Outcomes of Anatomical Lung Resections Using Video-Assisted Thoracoscopic Surgery and Thoracotomy Approaches - M. A. Atyukov; I. Yu. Zemtsova; A. S. Petrov; O. A. Zhemchugova-Zelenova; P. K. Yablonskiy (Инновационная медицина Кубани, 2024)
Objective: To analyze short-term outcomes of anatomical lung resections using video-assisted thoracoscopic surgery (VATS) and thoracotomy approaches.Materials and methods: Our retrospective study included 530 patients who underwent surgery for various lung diseases in the thoracic surgery unit of City Multidisciplinary Hospital No. 2 (Saint Petersburg, Russian Federation) between 2014 and 2021. The patients were grouped based on the surgical approach: group 1 for patients who underwent VATS (n = 378), group 2 for patients who underwent thoracotomy (n = 120), and group 3 for patients who underwent conversion from VATS to thoracotomy (n = 32).Results: Tumor size, paranodal and peribronchial changes were unfavorable prognostic factors for conversion from VATS to thoracotomy (odds ratio [OR] = 1.032, CI: 1.013-1.051, P < .001; OR = 4.416, CI: 2.100-9.283, P < .0005; OR = 3.109, CI: 1.496-6.462, P < .002). Patients from group 1 and group 3 mostly had minor complications, whereas 32 patients (53%) from group 2 developed grade III-V complications according to Thoracic Morbidity and Mortality classification system. High Charlson Comorbidity Index (CCI), thoracotomy approach, emphysematous changes, adhesions, and absence of interlobar fissures were independent unfavorable prognostic factors for complications in the early postoperative period (OR = 1.665, CI: 1.031-2.691, P < .05; OR = 1.874, CI: 1.1433.070, P < .05; OR = 1.8803, CI: 1.126-2.888, P < .05; OR = 1.548, CI: 1.010-2.370, P < .05; OR = 1.612, CI: 1.053-2.466, P < .05).Conclusions: VATS is an effective and safe approach for anatomical lung resection. Tumor size above 40 mm, significant paranodal and peribronchial changes were risk factors for conversion from VATS to thoracotomy. CCI above 5, thoracotomy approach, emphysematous changes, adhesions, and absence of interlobar fissures were independent unfavorable prognostic factors for complications in the early postoperative period.